Woody Species Composition, Diversity And Structure of Vegetation of Peri-Urban Park in Leo, Burkina Faso - Souleymane, Ganaba; Kadidia, Semdé; François, Kagambèga Wenemi; Moussa, Dao (European Scientific Journal, ESJ, 2021)
This work aims to fill a gap in knowledge of the Burkina Faso Southern Sudanese flora and vegetation. The woody vegetation of the forest park of the Scholl Complex in Léo comprises a total of 26 families, 63 genera and 81 species including native and introduced ones. The fallow is the unit that contains all families and genera and 93% of species. The most abundant species of units of the Park are Terminalia avicennioides (Combretaceae), Piliostigma thonningii (Fabaceae-Caesalpinioideae), Daniellia oliveri (Fabaceae-Caesalpinioideae), Vitellaria paradoxa (Sapotaceae), Detarium microcarpum (Fabaceae-Caesalpinioideae), Diospyros mespiliformis (Ebenaceae), Annona senegalensis (Annonaceae) and Pteleopsis suberosa (Combretaceae). The species that regenerate the most and that will ensure the sustainability of the peri-urban forest resources are Gardenia erubescens (Rubiaceae), Piliostigma reticulatum (Fabaceae-Caesalpinioideae), Vitellaria paradoxa, Annona senegalensis, Terminalia avicennioides (Combretaceae), Diospyros mespilifomis and Azadirachta indica (Meliaceae). The most threats on vegetation and flora of the School Complex are fraudulent human exploitation, parasitic pressure and progressive intrusion of Azadirachta indica. Peri-urban park resources conservation measures concern the replanting of vegetation in degraded areas and incentives for wood production for local populations. A management program for threatened or rare species, control of invasive alien plants and domestic animals and the development and improvement of habitat to create a future urban park.